Corneal donation in palliative care: a doctor's perspective. Issue 2 (1st September 2011) - Al-Qurainy, Rasha; Prentice, Wendy
Abstract : Introduction: Corneal donation is a possibility for many palliative care patients after death but anecdotal evidence suggests it is seldom done. Previous research in other settings (especially acute medical settings) suggest lack of knowledge and a negative attitude from staff contributing to low donation rates, rather than public refusal. Aim: To explore palliative care doctors' knowledge and attitudes about corneal donation and to find if any associations with corneal procurement exist. Methods and results: A postal survey was conducted that tested knowledge of corneal donation and asked about attitude and behaviour (past experiences). A 14 item questionnaire was sent to 427 practising palliative care consultants and associate specialists in the UK. A response rate of 50% was achieved and the findings were analysed using SPSS software and thematic content analysis. The study showed that over half (57%) of doctors had an inadequate level of knowledge about corneal donation but did have a positive personal and professional attitude towards it. There was a statistically significant association between their personal and professional attitude (ie, either both would be positive or both negative) with a significant association between a positive attitude and a higher mean knowledge score. The most common perceived drawback of discussing donation was fear of causing distress (36% of doctors gave this response). In practice, causing distress was reported by 4.8% of the doctors. Conclusion: The study found an association between palliative care doctors' knowledge and attitude with procurement behaviour. Those that viewed donation positively had a greater amount of knowledge. Doctors tended to have the same professional view as their personal view. This could suggest that doctors bring their personal opinions into the work place and exhibit gate-keeping behaviour which could have implications for practice. The study also highlighted the differences between doctors' perceptions and actual experiences.